On the Pathway to Success: Becoming a Leading Earth Observation Centre Through the EXCELSIOR Project - Hadjimitsis, Diofantos G.; Kouta, Georgia; Themistocleous, Kyriacos; Michaelides, Silas; Neocleous, Kyriacos; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Papoutsa, Christiana; Tzouvaras, Marios; Mettas, Christodoulos; Christofe, Andreas; Evagorou, Evagoras G.; et al. (My University, 2018)
This paper presents the pathway towards the establishment of the ERATOSTHENES Centre of Excellence (ECoE), through the upgrade of the existing Remote Sensing & Geo-Environment Group - ERATOSTHENES Research Centre (ERC), within the Cyprus University of Technology (CUT). The ECoE aspires to become a sustainable, viable and autonomous Centre of Excellence for Earth Surveillance and Space-Based Monitoring of the Environment. The ECoE will provide the highest quality of related services in the National, European, Eastern Mediterranean and Middle East and Northern Africa areas (EMMENA). Therefore, drawing on the capitalization of experience and knowledge from previous projects and the research areas and international networks of the ERC, this papers highlights the importance of the establishment of the ECoE in the EMMENA area.
Keywords: Centre of Excellence; Cultural heritage; Cyprus; Earth Observation; EMMENA; Environmental monitoring; Remote sensing; Smart specialization strategy